The Experience of Caring For Elderly Parents among Low-Income Malay Adult Children in Kuala Lumpur - Alavi, Khadijah (2008)
The main purpose of this study was to understand the nature of adult children caregivers’ experiences and how they manage their daily living activities while caring for older parents. The study was carried out to answer three research questions: i) what is the experience of adult children in taking care of elderly parents? ii) how do they manage their careers, own family and parents? and iii) what is the Islamic perspective on filial responsibility towards elderly parents in a challenging family and modern social environment? A case study guided by phenomenology was chosen as an approach in this study. Selected respondents were Malay adult children caring for elderly parents aged 60 and above, in low income families in Kuala Lumpur. Eight respondents were interviewed twice in a six month interval. Interviews were conducted and recorded using an IC recorder, transcribed verbatim and then analyzed using the constant comparative method. Analysis of authorized JKMM (Welfare Department of Malaysia) documents and systematic observation were used as focal points on physical facilities such as the housing environment. A round table discussion with policy makers, front liners/implementers, two respondents representing adult children, dissertation supervisor and committee members, and the researcher was conducted to validate the data of the study. The findings encompassed two major experiences among adult children, which include their experiences before (pre experience) and while (actual experience) taking care of elderly parents. The findings indicated that the adult children are overwhelmed by time constraints as well as financial, health, physical and socio-emotional stress. In managing caregiving, adult children caring for frail and disabled elderly parents face multiple burdens, challenges and problems in balancing their careers, own family and filial obligations, according to the Islamic perspective. Islamic teachings emphasizing the divine favour and honour associated with caring for parents were identified as a coping strategy to overcome their burden. Study respondents also received support from other family members, government agencies and non-government agencies in the process of taking care of their elderly parents. Strategic planning and program development recommendations for government, non-government, public higher education and local community institutions were put forth to help overcome the challenges and problems faced by adult child caregivers. Finally, the study concludes by emphasizing that one can learn much from his or her own experiences, but it is better to acquire knowledge through the experiences of others.